2014
DOI: 10.1007/s10620-014-3262-8
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Variability of Colonoscopy Preparation Instructions

Abstract: Despite national recommendations for use of split-dose bowel purgatives, many practices are still relying on single-dose preparations. Clear liquid diets are widely recommended for the day prior to the colonoscopy, despite a lack of data to support the need for such a strict dietary regimen. Patients receive disparate instructions regarding the management of their medications. These findings suggest a need for more evidence-based and comprehensive colonoscopy preparation instructions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Recent systematic reviews found that patient education interventions improve the quality of bowel preparation [7] and reduce anxiety about the procedure [8]. Clinical practices use a range of different materials to inform patients about colonoscopy preparation [9], but there has been limited evaluation of the quality of the materials used and limited efforts to improve the quality of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…Recent systematic reviews found that patient education interventions improve the quality of bowel preparation [7] and reduce anxiety about the procedure [8]. Clinical practices use a range of different materials to inform patients about colonoscopy preparation [9], but there has been limited evaluation of the quality of the materials used and limited efforts to improve the quality of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…A recent recommendation from the US Multi-Society Taskforce on Colorectal Cancer recommended that all patients receive both oral and written instructions before colonoscopy but did not specify how or when these instructions should be delivered [ 13 ]. With this lack of standardization, endoscopy centers often develop educational materials and processes locally, resulting in significant variation in the instructional content of written bowel preparation instructions [ 14 ]. In this context, the aim of this systematic review is to evaluate the efficacy of patient education interventions on the quality of bowel preparation among adults undergoing colonoscopy in prospective, controlled studies.…”
Section: Introductionmentioning
confidence: 99%
“…We know that significant variation still exists across the country in terms of bowel preparation instructions, including types of purgatives prescribed, use of split-dose versus single-dose preparations, dietary restrictions, and medication instructions. 7 However, there are some concrete suggestions that practices can take if they find their patients' bowel preparation adequacy rates falling below the suggested 85% benchmark. First, changing to split-dosing of the bowel purgative is an absolute must in 2016.…”
mentioning
confidence: 99%